34 Less radical fertility sparing than radical trachelectomy in early cervical cancer – 20 years experience. (18th September 2019) - Rob, L; Robova, H; Halaška, MJ; Pichlík, T; Drozenová, J; Pluta, M
Abstract : Objectives: Purpose of study was to determine long term experience of less radical surgery, sentinel lymph node identification (SLNI) with Tc 99 +blue day with laparoscopic surgery. Methods: From 1999 to 2018, 91 women with tumor less than 20 mm in largest diameter, infiltration less than half of cervical stroma underwent SLNI, frozen section (FS) of SLN, extirpation of afferent parametrial lymphatic channel, pelvic lymphadenectomy or only SLN. FS SLN positive patients underwent radical hysterectomy. Seven days after final histopathological processing of dissected nodes, large cone or simple trachelectomy was performed. Results: 15 women (16.5%) lost fertility. 9 women had positive lymph nodes (9.9%), 2 close invasive margin (2.2%), so radical hysterectomy was performed. Four cases had SIL in margin or patient decision, had laparoscopic hysterectomy. One patient N1 had recurrence and died of disease. All other are in complete remission. Fertility was save in 76 cases. Three central recurrences (isthmic part of uterus) were observed (3.9%), one died (1.3%), 2 are in CR 15 and 7 years. We have no distant recurrence. 62 of 76 women whose reproductive ability had been maintained tried to conceive (82%). Of these 62 women, 49 became pregnant (79%) in total 76 pregnancies. 43 mothers gave birth to 48 children, two children were by surrogate mothers. Conclusions: Less radical fertility sparing surgery in early cervical cancer can be feasible method that yields high, successful pregnancy rate. This work was supported by the Charles University research program PROGRES Q 28 (Oncology).